Clostridium butyricum enhances colonization resistance against Clostridioides difficile by metabolic and immune modulation - Mao Hagihara; Tadashi Ariyoshi; Yasutoshi Kuroki; Shuhei Eguchi; Seiya Higashi; Takeshi Mori; Tsunemasa Nonogaki; Kenta Iwasaki; Makoto Yamashita; Nobuhiro Asai; Yusuke Koizumi; Kentaro Oka; et al. (Scientific Reports, 2021)
Abstract Clostridioides difficile infection (CDI) represents the leading cause of nosocomial diarrhea worldwide and is associated with gut dysbiosis and intestinal damage. Clostridium butyricum MIYAIRI 588 (CBM 588) contributes significantly to reduce epithelial damage. However, the impacts of CBM 588 on antibacterial therapy for CDI are not clear. Here we show that CBM 588 enhanced the antibacterial activity of fidaxomicin against C. difficile and negatively modulated gut succinate levels to prevent C. difficile proliferation and downregulate tumor necrosis factor-α (TNF-α) producing macrophages in the colon lumina propria (cLP), resulting in a significant decrease in colon epithelial damage. Additionally, CBM 588 upregulated T cell-dependent pathogen specific immunoglobulin A (IgA) via interleukin (IL)-17A producing CD4+ cells and plasma B cells in the cLP, and Th17 cells in the cLP enhanced the gut epithelial barrier function. IL-17A and succinic acid modulations with CBM 588 enhance gut colonization resistance to C. difficile and protect the colon tissue from CDI.